Analisis Tingkat Kepuasan Mahasiswa Terhadap Penggunaan Sistem Informasi Akademik Menggunakan Metode PIECES Framework (Studi Kasus: Universitas Pembangunan Panca Budi) - Erika, Winda (Jurnal Mahajana Informasi, 2023)
Abstract: The academic information system is a very important system to help the lecture process become more effective and efficient. To evaluate the strengths and weaknesses of academic information systems, we need a method to see the level of user satisfaction. In this study the PIECES Framework method will be used to evaluate the level of student satisfaction in using the academic information system at Pembangunan Panca Budi University. The PIECES Framework method is a method used to evaluate a system consisting of performance , information, economics, control and security, efficiency, and the service to be analyzed. Data collection in the form of a questionnaire. Respondents will be used as many as 100 students from the computer systems study program. The results of the study show the level of user satisfaction with academic information systems meeting user needs.